2005
DOI: 10.1029/2004ja010778
|View full text |Cite
|
Sign up to set email alerts
|

On the relationships between double‐onset substorm, pseudobreakup, and IMF variation: The 4 September 1999 event

Abstract: [1] The relationships between double-onset substorm, pseudobreakup, and IMF variation were investigated with magnetic, auroral, and particle observations from space to the ground during 0200-0600 UT on 4 September 1999. There were five consecutive bursts of Pi2 pulsations on the ground during the time of interest. The onset time of ground Pi2s maps to the same variation sequence in the IMF structure seen propagating to the Earth in multiple satellite observations in the upstream region. The comparison of auror… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
(48 reference statements)
1
12
0
Order By: Relevance
“…7 for the aurora-related westward electrojet at the first onset to appear at lower latitude than that at the second onset for each activation period. This feature is consistent with the findings by Cheng et al (2005) with the meridian scanning photometer data. Namely, the above tendency in the INTERMAG-NET magnetograms justifies the inference on the source sites 600 C.-C. Cheng et al: THEMIS observations of double-onset substorms of two Pi2 bursts for each substorm through the spectral analysis in the aforementioned subsection.…”
Section: Intermagnet Magnetogramssupporting
confidence: 82%
See 2 more Smart Citations
“…7 for the aurora-related westward electrojet at the first onset to appear at lower latitude than that at the second onset for each activation period. This feature is consistent with the findings by Cheng et al (2005) with the meridian scanning photometer data. Namely, the above tendency in the INTERMAG-NET magnetograms justifies the inference on the source sites 600 C.-C. Cheng et al: THEMIS observations of double-onset substorms of two Pi2 bursts for each substorm through the spectral analysis in the aforementioned subsection.…”
Section: Intermagnet Magnetogramssupporting
confidence: 82%
“…More ground and space observations (e.g. Mishin et al, 2001;Cheng et al, 2005) demonstrated that nightside disturbances can have two or more onsets during a substorm sequence. However, these early studies did not have well-coordinated measurements for further verifications of the link of ground Pi2s with other substorm signatures in the nightside magnetosphere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is still unclear to what extent the fluctuations in the solar wind are reflected in the fluctuations of magnetosphere-ionosphere system. Numerous studies have tried to approach this problem by using both deterministic and stochastic paradigms (Tsurutani et al, 1990;Hnat et al, 2005;Cheng et al, 2005;Pulkkinen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The onset times of the two have only 3 min difference. In some previous studies (e.g., Cheng et al, 2005Cheng et al, , 2011, this kind of events was named as a double-onset substorm, which was explained as the effect of the reconnection at the near-earth neutral point on closed field line within the plasma sheet and on the open flux of tail lobes. However, if that is really the case, the second onset should be at latitudes higher than the first one, which is not the case in our event.…”
Section: Discussionmentioning
confidence: 99%